Field verification study on micropiles underpinning for ground improvement - Azuin Ramli; Zaihalem Zainal; Rufaizal Che Mamat (Penerbit Universiti Kebangsaan Malaysia, 2022)
Micropiles are mostly employed to resist static and seismic stresses and as an in-situ stabilizing device for slopes and excavations. A micropiles testing facility was designed to support the Light Rail Transit 3 (LRT3) project. A borehole of 150mm in diameter was used to install three micropiles that ranged in length from 3, 5, and 7 meters. This article explores the more detailed techniques used to complete foundation retrofits, with a focus on micropiles as a ground improvement method. The comparative analysis discussed the data obtained with the static load test and piles driving analyzer (PDA). This study found that the bearing capacity of Ru 177 tonnes and 111 tonnes are more than the load, which is calculated at 60.9 tonnes. Finally, several recommendations for further research were presented after evaluation to prevent micropiles damage was performed.